THE USE OF COOPERATIVE LEARNING TO IMPROVE THE STUDENTS' MOTIVATION AT THE ENGLISH READING CLASS - Prosawita Ririh Kusumasari (Jurnal Lingua Idea, 2018)
This research study inverstigated the effects of using cooperative learning to improve students’ motivation in first semester English class of law faculty in Wijaya Kusuma University Purwokerto. Motivation becomes some processes that controls and maintains certain behaviors. Everyone experiences lack of motivation from time to time. Some students sometimes get a sense that they are fear of failure. Furthermore, students need to have mastery experiences increase confidence and willingness to try interesting and more challenging tasks to build their motivation. Concerning the problems of teaching reading in the class, the study used cooperative learning method to find out whether cooperative learning technique could enhance students’ motivation in English class. Cooperative learning type in this class is used as group discussions. The design employed in this research was Classroom Action Research. The study was conducted at the first semester students in law faculty of Wijaya Kusuma University Purwokerto. The class consisted of 24 students. Observation, questionnaire, evaluation sheet and students’ reading test were implemented as instruments to collect the data. To measure students’ motivation there were five observation aspects. These five observation aspects measured when teaching learning activities in classroom. The teacher was observed and taking notes for each observation aspect. They were asking questions, answering question, active in discussion and share the information, comprehending text easily and enthusiastic in doing assignments. The five observation aspects also created a lot of influence and improvement based on the observation since first meeting till 8 meeting. The findings of the study can be concluded that cooperative learning method showed and improved students’ motivation.